Ne postoje suverene etničke zajednice u državi Bosni i Hercegovini / There are not Sovereign Communities in the State of Bosnia and Herzegovina - Tursić, Nermin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The paper‟s methodological basis deals with the issue of legitimacy and defining the titular sovereignty in the state of Bosnia and Herzegovina. On that trail, the paper studies the problem of categorizing the concept of "sovereign constituent peoples - could there be "sovereign Serbian", "sovereign Croatian" and "sovereign Bosniak" peoples in Bosnia and Herzegovina, and whether or not these terms are justified. Pursuant to the existing sovereignty theories and their practical application, the paper explicitly concludes that individual ethnic groups cannot bear sovereignty, but only in its totality as a political people of Bosnia and Herzegovina.